Development of 6 U CubeSat’s Deployable Solar Panel with Burn Wire Triggering Holding and Release Mechanism - Tae-Yong Park; Bong-Geon Chae; Hyun-Ung Oh (International Journal of Aerospace Engineering)
In the present work, a deployable solar panel based on a burn wire triggering holding and release mechanism was developed for use of 6 U CubeSat. The holding and release mechanism was designed based on a nichrome burn wire cutting method widely used for CubeSat applications. However, it provides a high loading capability, reliable wire cutting, multiplane constraints, and handling simplicity during the tightening process of wire. A demonstration model of a printed circuit board-based solar panel stiffened by a high-pressure fiberglass-laminated G10 material was fabricated and tested to validate the effectiveness of the design and functionality of the mechanism under various test conditions. The structural safety of the solar panel combined with the mechanism in a launch vibration environment was verified through sine and random vibration tests at qualification level.